Class structure in Sweden 1980 - Ahrne, Göran (Uppsala University, 1984)
The purpose of the survey is to describe and measure the Swedish class structure regarding mobility, political activity, attitudes and consciousness. A battery of questions addressed work-related issues such as supervision, decision-making, autonomy, respondents formal position in the hierarchy, ownership, credentials, and income. Other work-related data describe the size, industrial sector, and government or corporate linkage of the individuals employer. Further information was gathered on the class origins of the respondents family and of the families of the respondents spouse and friends. Data on class-related experiences such as unemployment and union participation were also collected, as well as data on the division of power and labour in the household. In addition the survey contained a broad range of questions on social and political attitudes and the respondents political participation. The study is part of the multinational study ´Class Structure and Class Consciousness´ (ICPSR 8413), which includes almost identificial studies from United States, Norway, Canada, and Finland.

The purpose of the survey is to describe and measure the Swedish class structure regarding mobility, political activity, attitudes and consciousness. A battery of questions addressed work-related issues such as supervision, decision-making, autonomy, respondents formal position in the hierarchy, ownership, credentials, and income. Other work-related data describe the size, industrial sector, and government or corporate linkage of the individuals employer. Further information was gathered on the class origins of the respondents family and of the families of the respondents spouse and friends. Data on class-related experiences such as unemployment and union participation were also collected, as well as data on the division of power and labour in the household. In addition the survey contained a broad range of questions on social and political attitudes and the respondents political participation. The study is part of the multinational study ´Class Structure and Class Consciousness´ (ICPSR 8413), which includes almost identificial studies from United States, Norway, Canada, and Finland.
Klasstrukturen i Sverige 1980
Keywords: OCCUPATIONS; YRKEN; EMPLOYMENT; ANSTÄLLNING; DOMESTIC RESPONSIBILITIES; HUSHÅLLSANSVAR; UNEMPLOYMENT; ARBETSLÖSHET; FRIENDS; VÄNNER; DECISION MAKING; BESLUTSFATTANDE; SELF-EMPLOYED; EGENFÖRETAGARE; SEASONAL EMPLOYMENT; SÄSONGSARBETE; TURNOVER; OMSÄTTNING; SUPERVISORY STATUS; ARBETSLEDANDE STÄLLNING; CRIME PREVENTION; BROTTSFÖREBYGGANDE ARBETE; SOCIAL CLASS; SOCIAL KLASS; POLITICAL PARTIES; POLITISKA PARTIER; STATUS IN EMPLOYMENT; TJÄNSTESTÄLLNING; TRADE UNIONS; FACKFÖRENINGAR; WORKING CONDITIONS; ARBETSFÖRHÅLLANDEN; HOURS OF WORK; ARBETSTID; GENDER EQUALITY; JÄMSTÄLLDHET; CRIME AND SECURITY; BROTT; Working conditions; Arbetsförhållanden; Equality, inequality and social exclusion; Jämlikhet, ojämlikhet och socialt utanförskap; Social Sciences; Samhällsvetenskap